- Manajemen Pemberian Pakan Dalam Budidaya Udang Vaname (Litopenaeus vannamei) Untuk Mencapai Pertumbuhan Yang Optimal di Tambak Intensif PT. Nusantara Veritas Trinitas, Bangka Belitung: - - Arif Darmawan; Titin Liana Febriyanti; M. Hadziq Qulubi (Fakultas Perikanan dan Kelautan. Universitas Khairun, 2026)
In the intensive Litopenaeus vannamei (vaname shrimp) farming operations managed by the technical service unit, feed management extends beyond the actual feeding process; proper feed storage is also crucial for preserving shelf life and nutritional value. This study aims to examine the feed management practices employed at PT. Nusantara Veritas Trinitas’s intensive farm in Bangka Belitung to achieve optimal L. vannamei growth—a focus that represents the study's novel contribution. Data collection was conducted through observation, involving participation in all activities related to the grow-out phase of L. vannamei. The research took place at the PT. Nusantara Veritas Trinitas intensive farm in Penagan Village, West Mendo District, Bangka Regency, utilizing both primary and secondary data. Analysis of the farming process reveals that effective feed management requires careful attention to feeding frequency, feeding methods, monitoring of feed trays (anco), and sampling procedures. Key metrics derived from sampling data include Average Body Weight (ABW), Average Daily Gain (ADG), Survival Rate (SR), biomass, and Feed Conversion Ratio (FCR). Calculations showed that at 40 days of culture (DOC), the highest FCR was 1.30 (Pond D9) and the lowest was 1.13 (Pond D7); at 50 DOC, the highest FCR was 1.25 (Pond D10) and the lowest was 1.12 (Pond D12). Overall, the cultivation process demonstrates that feed management—encompassing feeding frequency and techniques, anco monitoring, and sampling—constitutes an integrated system that significantly influences farming success.